Afghanistan in Transition: Looking beyond 2014 - Hogg, Richard (World Bank, 2015)
The withdrawal of most international troops by 2014 will have a profound and lasting impact on the country's economic and development fabric. This book explores some of these ramifications. Development progress since 2001 has been mixed. The country has recorded some major achievements such as rapid economic growth, relatively low inflation, better public financial management, and gains in basic health and education. Key social indicators, including life expectancy and maternal mortality, have improved markedly, and women are participating more in the economy. Yet in other respects, particularly governance and institution building, the country has fared less well, and many indicators have worsened in recent years. Afghanistan remains one of the world's least developed countries, with a per capita gross domestic product (GDP) of only $528. More than a third of the population live below the poverty line, more than half are vulnerable and at serious risk of falling into poverty, and three-quarters are illiterate. Additionally, political uncertainty and insecurity could undermine Afghanistan's transition and development prospects.